Дискретизация теоремы Лебега-Колмогорова - А. Л. Григорян (Հայաստանի ԳԱԱ)
Пусть Wr - класс функций периода 2π- имеющих r-ую производную, удовлетворяющую условию jf(r)(x)j ≤1. Абсолютное значение остаточного члена ряда Фурье функции f(x) 2 Wr имеет для этого класса функций конечную, не зависящую от x верхнюю грань Cr m . А. Н. Колмогоровым доказана следующая теорема: Для любого натурального r справедлива асимптотическая формула Crm = m-r • ( 4 π2 • lnm + O(1) ) . Цель настоящей работы - доказать, что дискретизация непрерывной задачи не только представляет самостоятельный интерес, но и является одним из подходов ее решения. Let Wr be the space of 2π-periodic functions f(x) that are continuous together with their derivatives of order r (r ∈ N), and satisfy the condition |f(r)(x)| ≤ 1. The absolute value of the remainder of the Fouries series of function f(x) ∈ Wr has a finite upper bound which does not depend on x. A. N. Kolmogorov obtained the following result: For any natural r the following asymptotic relation holds Crm = m-r • ( 4 π2 • lnm + O(1) ) . The aim of the present paper is to prove that discretization of the above continuous problem is one of the possible approaches of its solution.
Keywords: Science; Mathematics